Draft Annual Plan 1991-92 Volume I (Narrative) Government of Rajasthan - Planning Commission (Planning Commission, 1990)
The Agriculture Extension Education and Research hither to being looked after till 1st August, 1987, by the Mohan Lal Sukhadia University, Udaipur is now being looked after by the Rajasthan Agriculture University, Bikaner. the University will carry out production—or intend research programmes, rural mass education and adoption and propagation of new technologies in the State in the field of agriculture.
Planning Department Government of Rajasthan